2019
DOI: 10.1103/physrevb.99.104416
|View full text |Cite
|
Sign up to set email alerts
|

Current-driven skyrmion depinning in magnetic granular films

Abstract: We consider current-driven motion of magnetic skyrmions in granular magnetic films. The study uses micromagnetic modeling and phenomenological analysis based on the Thiele formalism. Remarkably, disorder enhances the effective skyrmion Hall effect that depends on the magnitude of the driving force (current density and non-adiabaticity parameter). The origin is sliding motion of the skyrmion along the grain boundaries, followed by pinning and depinning at the grain junctions. A side-jump can occur during this d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…2. Although the critical current densities and skyrmion velocities for which the depinning and flow regimes are reached depend on the choice of disorder parameters [22,23,48], this approach constitutes a good qualitative description of the pinning effect on the current-driven skyrmion dynamics. Qualitatively, the micromagnetic simulations reveal that the disorderfree velocity and SkHA constitute upper bounds for the velocity and SkHA in disordered systems.…”
Section: Micromagnetic Simulationsmentioning
confidence: 99%
“…2. Although the critical current densities and skyrmion velocities for which the depinning and flow regimes are reached depend on the choice of disorder parameters [22,23,48], this approach constitutes a good qualitative description of the pinning effect on the current-driven skyrmion dynamics. Qualitatively, the micromagnetic simulations reveal that the disorderfree velocity and SkHA constitute upper bounds for the velocity and SkHA in disordered systems.…”
Section: Micromagnetic Simulationsmentioning
confidence: 99%
“…Previous studies have shown how a threshold current arises due to confining pinning potentials 41,42 , defect scattering 43,44 , polycrystalline structures with crystallites of varying anisotropy axes orientation 45 , disorder originating from M S fluctuations using a granular structure 46 , as well as disorder in the DMI 7,8 and anisotropy constant 7,11 . Imperfections have also been shown to result in a change of the skyrmion Hall angle with skyrmion velocity due to sliding motion along grain boundaries 45 . Another mechanism which results in variation of the skyrmion Hall angle with velocity is due to the field-like SOT component in combination with breathing skyrmion modes 47,48 , or deformations and internal mode excitations 10 .…”
Section: Threshold Currentsmentioning
confidence: 99%
“…In addition, their topological signatures make skyrmion detection in ferromagnets rather simple [35]. Besides these attractive features, ferromagnetic skyrmions also experience current-driven gyroscopic forces that can limit their scalability [31,32,36]. On the other hand, it was recently suggested that such gyroscopic forces could be exploited to enhance the mobility of a train of skyrmions in ferromagnetic nanotracks [37].…”
Section: Introductionmentioning
confidence: 99%